Preparation method and application of organic-inorganic composite soybean protein gel adhesive
By introducing organic-inorganic composite soy protein gel and polymer coating into the hydrogel, the problems of poor mechanical properties and weak bonding properties of traditional hydrogels were solved, and organic inorganic composite hydrogels with high strength and high bonding properties were prepared, expanding their application prospects in the fields of biomedical and flexible electronics.
Patent Information
- Application Number
- CN202311837274.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-12-28
AI Technical Summary
Traditional hydrogels have poor mechanical properties and weak adhesive properties during application, which limits their application scope in biomedical and flexible electronic fields.
Using the preparation method of organic-inorganic composite soy protein gel adhesive, the soy protein is dispersed in deionized water, and chemical substances such as sodium alginate and acrylamide are added after heating, and the polymerization reaction and soaked in the salt solution is carried out to form a high-strength organic and inorganic composite hydrogel, and a polymer coating is applied to its surface to improve the adhesive performance.
The prepared organic and inorganic composite hydrogel has high cohesion, tearing energy and bonding strength, which significantly improves its mechanical properties and bonding properties, and is suitable for biomedical and flexible electronic fields.
Smart Images

Figure CN117924770B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bio-based hydrogels, and specifically relates to a preparation method and application of an organic-inorganic composite soybean protein gel adhesive. Background Art
[0002] Hydrogels are 3D polymer networks cross-linked by physical interactions or covalent bonds. They are polymers that are insoluble in water but have high swelling properties. Hydrogels have extraordinary commercial potential in daily necessities, biomedicine, environmental engineering, food science, flexible electronics and other fields.
[0003] However, in the application process, hydrogels are required to form interfaces not only with biological tissues, but also with electronic devices, etc. The poor mechanical properties and poor adhesive properties of traditional hydrogels have severely limited the scope of application of hydrogels.
[0004] Soy protein is one of the better environmentally friendly biomass because it is biodegradable, abundant, renewable annually, cheap, non-toxic, easy to handle, and has great potential in industry. Sodium alginate is a derivative of alginate, which appears as a light yellow or white powder. It is a polyanionic polysaccharide that can form a three-dimensional gel structure by cross-linking molecular chains using ions. Both soy protein and sodium alginate are environmentally friendly and renewable natural products. Adding sodium alginate to hydrogel can improve the mechanical properties of hydrogel. However, hydrogels prepared solely from raw materials such as soy protein and sodium alginate still have weak adhesion. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an organic-inorganic composite soybean protein gel adhesive.
[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing an organic-inorganic composite soybean protein gel adhesive, comprising:
[0009] Dispersing soybean protein in deionized water and heating to obtain a soybean protein dispersion;
[0010] adding sodium alginate, acrylamide, hydroxyapatite, N,N-methylenebisacrylamide, ammonium persulfate, and N,N,N′,N′-tetramethylenediamine into a soybean protein dispersion to prepare a precursor solution;
[0011] The precursor solution is heated for polymerization reaction and then immersed in a salt solution to obtain an organic-inorganic composite hydrogel;
[0012] Methoxyethyl acrylate, N-(3,4-dihydroxyphenyl)methacrylamide and 2,2-azobisisobutyronitrile are mixed in N,N-dimethylformamide, and heated under N2 atmosphere and stirred for 10 to 12 hours to obtain a poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer;
[0013] The poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer is applied to the organic-inorganic composite hydrogel whose surface is soaked with a tannin solution to prepare the organic-inorganic composite hydrogel having a coating with excellent bonding properties.
[0014] As a preferred embodiment of the preparation method of the present invention, the concentration of the soybean protein dispersion is 0 to 9 wt.%.
[0015] As a preferred embodiment of the preparation method of the present invention, wherein: sodium alginate is added to the soybean protein dispersion, wherein the ratio of sodium alginate to soybean protein is 1:0 to 1:4.5.
[0016] As a preferred embodiment of the preparation method of the present invention, the mass ratio of acrylamide, hydroxyapatite, N,N-methylenebisacrylamide, ammonium persulfate and N,N,N′,N′-tetramethylenediamine is 1:0.1:0.0028:0.0107:0.0056; and the mass ratio of acrylamide to soy protein is 1:0 to 1:0.75.
[0017] As a preferred embodiment of the preparation method of the present invention, the precursor solution is heated for polymerization reaction, wherein the heating reaction temperature is 60° C. and the reaction time is 3 hours.
[0018] As a preferred embodiment of the preparation method of the present invention, the immersion in salt solution comprises a zinc chloride aqueous solution having a concentration of 3 m.
[0019] As a preferred embodiment of the preparation method of the present invention, the mass ratio of methoxyethyl acrylate, N-(3,4-dihydroxyphenyl)methacrylamide and 2,2-azobisisobutyronitrile is 1:0.34:0.0212.
[0020] As a preferred embodiment of the preparation method of the present invention, the organic-inorganic composite hydrogel after the surface is infiltrated with tannin solution, wherein the surface infiltration method of the organic-inorganic composite hydrogel comprises:
[0021] The organic-inorganic composite hydrogel is immersed in a 1-5% tannin solution for 0.5-2 hours, and then rinsed with deionized water to remove excess tannin;
[0022] The tannin-containing hydrogel was immersed in a 3 M zinc chloride solution for 0.5 to 1 h, and the excess ZnCl2 was removed with deionized water;
[0023] Wait for the water on the surface of the obtained hydrogel to dry.
[0024] Another object of the present invention is to overcome the deficiencies in the prior art and provide an organic-inorganic composite soybean protein gel adhesive.
[0025] Another object of the present invention is to overcome the deficiencies in the prior art and provide an organic-inorganic composite soybean protein gel adhesive for use in biomedicine and flexible electronics.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention provides a new idea. A high-strength organic-inorganic composite hydrogel is used as a matrix. On this basis, a polymer coating is introduced to prepare a coated organic-inorganic composite hydrogel with excellent bonding properties. The prepared organic-inorganic composite hydrogel has high cohesion and higher tear energy and bonding strength than traditional hydrogels, which is beneficial to improving the current problems of poor mechanical properties and weak bonding of hydrogels.
[0028] (2) The composite hydrogel prepared by the present invention has universal adhesion and has potential application prospects in the fields of biomedicine, flexible electronics, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0030] Figure 1 This is a scanning electron microscope image of the organic-inorganic composite hydrogel in an embodiment of the present invention.
[0031] Figure 2: are the stress-strain curves of the organic-inorganic composite hydrogel and the tear energy diagram of the organic-inorganic composite hydrogel in the embodiment of the present invention, wherein a is the stress-strain curve diagram of the prepared organic-inorganic composite hydrogel, and b is the tear energy diagram of the prepared organic-inorganic composite hydrogel.
[0032] Figure 3 These are actual pictures and result diagrams of the interface toughness and lap shear test between the coated organic-inorganic composite hydrogel and the zinc sheet prepared in the embodiments of the present invention, wherein a is a peeling process diagram of the organic-inorganic composite hydrogel without a coating, b is a peeling process diagram of the PAAm / SPI hydrogel, c is an interface toughness test curve, and d is a lap shear test curve diagram.
[0033] Figure 4 This is a physical picture of the bonding of the organic-inorganic composite hydrogel containing a coating prepared in the examples of the present invention with materials such as glass, polypropylene (PP), polytetrafluoroethylene (PTFE), weights, rubber, wood and steel ruler. DETAILED DESCRIPTION
[0034] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0035] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0037] Example 1
[0038] Preparation of organic-inorganic composite hydrogel:
[0039] (1) First, 0.9 g of soy protein isolate was dispersed in 30 mL of deionized water at 95 °C for 4 h to obtain a soy protein dispersion;
[0040] (2) Then, 0.6 g of sodium alginate, 3.6 g of acrylamide, 0.72 g of hydroxyapatite, 0.0102 g of N,N-methylenebisacrylamide, 0.0384 g of ammonium persulfate and 20 μL of N,N,N′,N′-tetramethylenediamine were mixed in the soybean protein dispersion solution to form a uniform precursor solution, in which acrylamide and sodium alginate were filled as organic phases and hydroxyapatite was filled as an inorganic phase.
[0041] (3) The mixture was transferred into a sealed glass mold (10 mm×10 mm×2 mm) and reacted in an oven at 60°C for 3 h.
[0042] (4) Finally, the sample was immersed in a 3 M zinc chloride solution for 12 h to obtain an organic-inorganic composite hydrogel. The scanning electron microscopy image of the organic-inorganic composite hydrogel is shown in Figure 1 .
[0043] Example 2
[0044] Preparation of sodium alginate (SA) hydrogel:
[0045] (1) Dissolve 0.6 g of sodium alginate in 30 mL of deionized water to form a uniform solution;
[0046] (2) Then, the solution was transferred into a glass mold (10 mm × 10 mm × 2 mm) with one side open;
[0047] (3) Finally, the entire glass mold was placed in a 3 M zinc chloride salt solution and soaked for 12 h to obtain SA hydrogel.
[0048] Example 3
[0049] Preparation of polyacrylamide / soy protein (PAAm / SPI) hydrogel:
[0050] (1) First, 0.9 g of soy protein isolate was dispersed in 30 mL of deionized water at 95 °C for 4 h to obtain a soy protein dispersion;
[0051] (2) Then, 3.6 g of acrylamide, 0.0102 g of N,N-methylenebisacrylamide, 0.0384 g of ammonium persulfate, and 20 μL of N,N,N′,N′-tetramethylenediamine were mixed in the soybean protein dispersion solution to form a uniform precursor solution;
[0052] (3) The mixture was transferred into a closed glass mold (10 mm × 10 mm × 2 mm) and reacted in an oven at 60 °C for 3 h to obtain PAAm / SPI hydrogel.
[0053] Example 4
[0054] Preparation of polyacrylamide-sodium alginate / soy protein (PAAm-SA / SPI) hydrogel:
[0055] (1) First, 0.9 g of soy protein isolate was dispersed in 30 mL of deionized water at 95 °C for 4 h to obtain a soy protein dispersion;
[0056] (2) Then, 0.6 g of sodium alginate, 3.6 g of acrylamide, 0.0102 g of N,N-methylenebisacrylamide, 0.0384 g of ammonium persulfate, and 20 μL of N,N,N′,N′-tetramethylenediamine were mixed in the soybean protein dispersion solution to form a uniform precursor solution.
[0057] (3) The mixture was transferred into a sealed glass mold (10 mm×10 mm×2 mm) and reacted in an oven at 60°C for 3 h.
[0058] (4) Finally, the sample was immersed in 3 m zinc chloride salt solution for 12 h to obtain PAAm-SA / HAp hydrogel.
[0059] Example 5
[0060] Preparation of poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer coating:
[0061] The poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer coating was synthesized by free radical polymerization.
[0062] (1) 1.25 g of methoxyethyl acrylate, 0.425 g of N-(3,4-dihydroxyphenyl)methacrylamide, and 0.0265 g of 2,2-azobisisobutyronitrile were mixed in 2.5 mL of N,N-dimethylformamide and stirred at 80°C under N2 atmosphere for 10 to 12 h.
[0063] (2) After completion, the reaction mixture was purified three times by dissolution with ethyl acetate and precipitation with n-hexane.
[0064] (3) Then, the copolymer was dried in a vacuum dryer to obtain a light yellow solid.
[0065] Example 6
[0066] Polymer coating application method:
[0067] The polymer coating is coated on the organic-inorganic composite hydrogel.
[0068] (1) First, the organic-inorganic composite hydrogel was immersed in a 5% tannin solution for 0.5 h and then rinsed with deionized water to remove excess tannin.
[0069] (2) The tannin-containing hydrogel was immersed in a 3 M zinc chloride solution for 0.5 h, and the excess ZnCl2 was removed with deionized water.
[0070] (3) After the water on the surface of the obtained hydrogel is dried, a dichloromethane solution containing poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) is applied thereon to obtain an organic-inorganic composite hydrogel containing a coating.
[0071] Example 7
[0072] Tensile properties of organic-inorganic composite hydrogels:
[0073] The tensile properties of organic-inorganic composite hydrogels were tested using an electronic universal testing machine.
[0074] The organic-inorganic composite hydrogels prepared in the above Examples 1-4 were cut into rectangles (length 50 mm, width 20 mm, thickness 2.5 mm).
[0075] The sample was then fixed between stretching fixtures and uniaxial stretching was applied in the vertical direction at a stretching rate of 50 mm / min to obtain the tensile stress-strain curve of the organic-inorganic composite hydrogel.
[0076] The hydrogels prepared in Examples 2, 3 and 4 are comparative examples. Figure 2 As shown, the mechanical properties of the hydrogels prepared in Examples 1-4 are significantly different, the hydrogel prepared in Example 2 has excellent Young's modulus, and the hydrogel prepared in Example 3 has excellent fracture strain. The organic-inorganic composite hydrogel greatly improves the strength and stiffness of the hydrogel due to the simultaneous introduction of sodium alginate and soy protein, and the fracture stress, modulus and elongation at break are 340 kPa, 192 kPa and 313% respectively.
[0077] Example 8
[0078] Adhesive properties of coated organic-inorganic composite hydrogels:
[0079] The bonding properties of the coated organic-inorganic composite hydrogel were tested using an electronic universal testing machine.
[0080] Zinc sheet and carbon nanotube paper were selected as bonding substrates, and their interface toughness and lap shear strength were tested.
[0081] For the interface toughness test and the lap shear test, taking the coated organic-inorganic composite hydrogel prepared in Examples 1, 5 and 6 as an example, the bonding area between the prepared coated organic-inorganic composite hydrogel and the substrate was controlled to be 80 mm long and 25 mm wide or 25 mm long and 10 mm wide.
[0082] A polyethylene terephthalate (PET) film was coated on the back of the hydrogel as a hard backing pad to prevent it from stretching in the shear direction, and the stretching rate was 50 mm / min.
[0083] The interface toughness is obtained by dividing the plateau force and twice the plateau force by the adhesion width; the shear strength is determined by dividing the maximum force by the adhesion area.
[0084] The results of interface toughness and shear strength are shown in Figure 3 As shown in the figure, the hydrogel prepared in Example 3 failed due to cohesive failure (interface toughness and shear strength were 34 J m -2 and 17 kPa); the hydrogel prepared in Example 1 without polymer coating failed due to weak interfacial interaction (19 J m-2 and 16 kPa); while the organic-inorganic composite hydrogel containing coating had high cohesion and excellent bonding properties, so that the interface toughness and shear strength were higher than 320 J m-2 and 45 kPa, respectively.
[0085] Therefore, the strong bonding is achieved by the synergistic effect of the organic-inorganic hybrid hydrogel with high cohesion and the polymer coating with interfacial interaction.
[0086] Example 9
[0087] Universal bonding of coated organic-inorganic composite hydrogels:
[0088] Physical images of the universal bonding were obtained by attaching the coated organic-inorganic composite hydrogel with a length of 25 mm and a width of 25 mm to glass, polypropylene (PP), polytetrafluoroethylene (PTFE), weights, rubber, wood and a steel ruler, respectively.
[0089] From the attached Figure 4 It can be seen that the coated organic-inorganic composite hydrogel can be firmly bonded to various materials, which is mainly due to the fact that the rich catechol groups in the polymer coating can form a large number of chemical bonds with the surfaces of different bonding substrates. The synergistic effect of the organic-inorganic composite hydrogel with high cohesion and the polymer coating with interfacial interaction achieves strong bonding.
[0090] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing an organic-inorganic composite soybean protein gel adhesive, characterized in that: include, Dispersing soybean protein in deionized water and heating to obtain a soybean protein dispersion; adding sodium alginate, acrylamide, hydroxyapatite, N,N-methylenebisacrylamide, ammonium persulfate, and N,N,N′,N′-tetramethylenediamine into a soybean protein dispersion to prepare a precursor solution; The precursor solution is heated for polymerization reaction and then immersed in a salt solution to obtain an organic-inorganic composite hydrogel; Methoxyethyl acrylate, N-(3,4-dihydroxyphenyl)methacrylamide and 2,2-azobisisobutyronitrile were mixed in N,N-dimethylformamide, and heated under N2 atmosphere with stirring for 10-12 h to obtain poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer; The organic-inorganic composite soy protein gel adhesive was prepared by applying poly(methoxyethyl acrylate-N-(3,4-dihydroxyphenyl)methacrylamide) polymer on the organic-inorganic composite hydrogel whose surface was soaked in tannin solution.
2. The preparation method according to claim 1, characterized in that: The soy protein dispersion, wherein the ratio of soy protein to deionized water is 0.9 g:30 mL.
3. The preparation method according to claim 1 or 2, characterized in that: Sodium alginate is added to the soy protein dispersion, wherein the ratio of sodium alginate to soy protein is 0.6 g:0.9 g.
4. The preparation method according to claim 3, characterized in that: The ratio of acrylamide, hydroxyapatite, N,N-methylenebisacrylamide, ammonium persulfate and N,N,N′,N′-tetramethylenediamine is 3.6 g: 0.72 g: 0.0102 g: 0.0384 g: 20 μL; the ratio of acrylamide to soy protein is 3.6 g: 0.9 g.
5. The preparation method according to claim 1, characterized in that: The precursor solution is heated for polymerization reaction, wherein the heating reaction temperature is 60° C. and the reaction time is 3 h.
6. The preparation method according to claim 1, characterized in that: The soaking salt solution, wherein the salt solution includes a zinc chloride aqueous solution, and its concentration is 3M.
7. The preparation method according to claim 1, characterized in that: The mass ratio of the methoxyethyl acrylate, N-(3,4-dihydroxyphenyl)methacrylamide and 2,2-azobisisobutyronitrile is 1:0.34:0.0212.
8. The preparation method according to claim 1, characterized in that: The organic-inorganic composite hydrogel after the surface is infiltrated with tannin solution, wherein the surface infiltration method of the organic-inorganic composite hydrogel comprises: The organic-inorganic composite hydrogel was immersed in a 1-5% tannin solution for 0.5-2 h and then rinsed with deionized water to remove excess tannin; The tannin-containing hydrogel was immersed in 3 M zinc chloride solution for 0.5–1 h, and the excess ZnCl2 was removed with deionized water; Wait for the water on the surface of the obtained hydrogel to dry.
9. The organic-inorganic composite soybean protein gel adhesive prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the organic-inorganic composite soybean protein gel adhesive according to claim 9 in biomedicine and flexible electronics.
Citation Information
Patent Citations
Alginate / hydroxyapatite super-long nanowire composite hydrogel
CN106565974A
Soybean protein composite hydrogel with expansibility and adhesion and preparation method of soybean protein composite hydrogel
CN111574729A